New Perspectives on Early Modern Dutch Atlantic Slavery and Slave Trade - Van Rossum, Matthias (TSEG - The Low Countries Journal of Social and Economic History, 2022)
This Special Issue explores new routes in the economic historical research on the Dutch Atlantic history of slavery and slave trade. Each of its contributions tackles important blind spots that have continued to haunt Dutch economic history despite the recent energetic revival of research and debates on the economic impact of Dutch Atlantic slavery. Together, the articles of this Special Issue challenge our perspectives, questions and methods.